Purandare Hysteropexy Technique in a 28-year-old Female with Pelvic Organ Prolapse Stage III: A Rare Case Report - Putra, I Gede Mega; Kawilarang, Stella (BALI MEDICAL JOURNAL, 2016)
Background: Pelvic organ prolapse is rarely found in reproductive-age women or in women with low parity. However, the finding has be further investigated to determine any risk factor involved, as well as to decide on the most appropriate management. This case report discusses the management of Purandare hysteropexy in a 28-year-old female with pelvic organ prolapse stage III. Case: A conservative surgical management on a reproductive-age woman with pelvic organ prolapse stage III, who wants to preserve her uterus. Result: The patient had an anatomical reconstruction. She had a better quality of life after the Purandare hysteropexy, and had less complains. Conclusion: Purandare hysteropexy is one of the conservative surgical management on reproductive-age women with pelvic organ prolapse who still wants to conserve their uterus or reproductive organ